Coating, battery and vehicle comprising the same
By applying coatings of negative thermal expansion materials and/or zero thermal expansion materials on the separator of lithium-ion batteries, the problem of easy fuse and insufficient liquid absorption capacity of battery separator at high temperatures is solved, and the heat resistance and safety of the battery are significantly improved. .
Patent Information
- Application Number
- CN202210285152.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-03-22
AI Technical Summary
The existing lithium-ion battery separators are prone to fuse and breakage and short circuit at high temperatures, and the liquid absorption and liquid retention capabilities are poor, making it difficult to ensure that the battery has good heat resistance and shrinkage resistance under large temperature changes.
A coating comprising a negative thermal expansion material and/or a zero thermal expansion material is provided between the positive electrode of the battery and/or between the negative electrode and the isolator to improve the heat resistance and shrinkage resistance of the battery.
By using coatings of negative thermal expansion materials and/or zero thermal expansion materials, the thermal resistance and thermal shock strength of the battery membrane are significantly improved, ensuring the thermal stability and safety of the battery under large temperature changes.
Smart Images

Figure CN116825949B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a coating, a battery and a vehicle comprising the coating. Background Art
[0002] In recent years, with the increasing demand for battery life and lightness of mobile electronic devices, the development of lithium-ion secondary batteries with higher energy density has become the main technical direction.
[0003] At present, most commercial lithium-ion batteries are based on polyolefin separators, modified polyolefin separators or multilayer polyolefin separators. Such separators are prone to melting and breaking at high temperatures, resulting in short circuits in contact between the positive and negative electrodes, and are easily pierced by metal impurities during the production process, forming micro short circuits, resulting in high self-discharge of the battery. At the same time, polyolefin separators, modified polyolefin separators and multilayer polyolefin separators have poor liquid absorption and liquid retention capabilities. The ceramic coating on the surface of the existing separator is mainly made of aluminum oxide, boehmite, magnesium hydroxide, silicon dioxide, aluminum silicate, etc. Although such traditional materials can improve the heat resistance, puncture resistance and liquid absorption capacity of the separator to a certain extent, it is still difficult to overcome the large thermal stress generated at high temperatures, so it is difficult to ensure that the battery separator has good heat resistance and shrinkage resistance, as well as high heat shock resistance under large or rapid temperature changes. In addition, the above problems also exist for separators in all-solid-state batteries or semi-solid-state batteries. Therefore, as the coating material needs to be optimized to further improve battery performance, it is necessary to adapt to more demanding battery use environments. Summary of the invention
[0004] In view of this, the present application provides a coating suitable for a battery, wherein the coating comprises a negative thermal expansion material and / or a zero thermal expansion material; the coating is disposed between a positive electrode and a separator and / or between a negative electrode and a separator of the battery.
[0005] The coating has good heat resistance and shrinkage resistance, as well as high heat shock resistance, so that the battery has good thermal stability and safety.
[0006] Specifically, in the first aspect, the present application provides a coating suitable for a battery, the battery comprising a positive electrode, a negative electrode and a separator arranged between the positive electrode and the negative electrode, the coating comprising a negative thermal expansion material and / or a zero thermal expansion material; the coating is arranged between the positive electrode and the separator and / or between the negative electrode and the separator, and the coating is arranged on the surface of at least one of the separator, the positive electrode and the negative electrode.
[0007] “The coating includes negative thermal expansion material and / or zero thermal expansion material” can be understood as that the coating includes at least one of negative thermal expansion material and zero thermal expansion material, that is, the coating includes negative thermal expansion material, or the coating includes zero thermal expansion material, or the coating includes both negative thermal expansion material and zero thermal expansion material.
[0008] “The coating is arranged between the positive electrode and the separator and / or between the negative electrode and the separator” can be understood as that the location where the coating is arranged includes at least one of between the positive electrode and the separator and between the negative electrode and the separator, that is, the coating is arranged between the positive electrode and the separator, or the coating is arranged between the negative electrode and the separator, or the coating is arranged between the positive electrode and the separator and between the negative electrode and the separator at the same time.
[0009] The separator is a component in a battery that separates the positive and negative electrodes to prevent the two electrodes from contacting and short-circuiting, and allows electrolyte ions to pass through. It can be a common separator base film in the battery field, or a solid electrolyte or gel electrolyte in an all-solid-state battery or a semi-solid-state battery. The battery can be a lithium-ion battery, a sodium-ion battery, a magnesium-ion battery, etc.
[0010] In some embodiments of the present application, the negative thermal expansion material and / or the zero thermal expansion material is in a granular form, and the average particle size of the negative thermal expansion material and / or the zero thermal expansion material is 0.01 μm-5 μm.
[0011] In some embodiments of the present application, the negative thermal expansion material and / or zero thermal expansion material is in fibrous form, and the average fiber diameter of the negative thermal expansion material and / or zero thermal expansion material is 10 nm-500 nm, and the average fiber length is 0.5 μm-100 μm.
[0012] In some embodiments of the present application, the negative thermal expansion material and / or zero thermal expansion material is a combination of a granular material and a fibrous material; the average particle size of the granular material is 0.01 μm-5 μm; the average fiber diameter of the fibrous material is 10 nm-500 nm, and the average fiber length is 0.5 μm-100 μm.
[0013] In some embodiments of the present application, the surface layer of at least one of the separator, the positive electrode and the negative electrode close to the coating contains the negative thermal expansion material and / or the zero thermal expansion material.
[0014] In some embodiments of the present application, the average linear expansion coefficient a of the negative thermal expansion material in the temperature range of 25°C to 600°C satisfies: -30×10 -6 K -1 ≤a<0.
[0015] In some embodiments of the present application, the negative thermal expansion material and / or zero thermal expansion material is at least one of ZrW2O8, HfW2O8, ZrMo2O8 and AM2O7, A is at least one of Th, Zr, Hf and Sn, and M is at least one of P and V.
[0016] In some embodiments of the present application, the mass proportion of the negative thermal expansion material and / or the zero thermal expansion material in the coating is 63.3%-98.5%.
[0017] In some embodiments of the present application, the coating also includes a ceramic material, and the mass ratio of the ceramic material and the negative thermal expansion material and / or zero thermal expansion material in the coating is 63.3%-98.5%, and the mass ratio of the negative thermal expansion material and / or zero thermal expansion material to the ceramic material is 1:0-0:1.
[0018] In some embodiments of the present application, the ceramic material is at least one of aluminum oxide, boehmite, magnesium hydroxide, silicon dioxide and aluminosilicate.
[0019] In the implementation manner of the present application, the coating further includes a binder, and the mass proportion of the binder in the coating is 1%-35%.
[0020] In the embodiment of the present application, the coating has a porous structure; the thickness of the coating is 0.5 μm-5 μm.
[0021] In a second aspect, the present application provides a method for preparing a coating, comprising the following steps:
[0022] Dispersing and mixing the negative thermal expansion material and / or the zero thermal expansion material with the binder to obtain a coating slurry; or
[0023] Dispersing and mixing the ceramic material, the negative thermal expansion material and / or the zero thermal expansion material with the binder to obtain a coating slurry;
[0024] The coating slurry is coated on the surface of at least one of the separator, the positive electrode and the negative electrode of the battery, and dried to obtain a coating disposed between the positive electrode and the separator and / or between the negative electrode and the separator of the battery.
[0025] In the implementation manner of the present application, the mass percentage concentration of the binder dispersion is 2%-30%.
[0026] In the embodiment of the present application, the dispersion of the negative thermal expansion material and / or the zero thermal expansion material contains a dispersant, and the mass ratio of the negative thermal expansion material and / or the zero thermal expansion material to the dispersant is 1:0.005-1:0.08.
[0027] The dispersant comprises a coupling agent and a surfactant; the coupling agent is at least one of a chromium coupling agent, a silane coupling agent, a titanate coupling agent and an aluminate coupling agent; the surfactant is at least one of stearic acid, sodium dodecylphenyl yellow acid, a quaternary ammonium compound, lecithin, fatty acid glyceride and polysorbate.
[0028] The preparation method provided in the second aspect of the present application has low cost and high efficiency and is suitable for large-scale production.
[0029] In a third aspect, the present application provides a battery comprising a positive electrode, a negative electrode and a separator arranged between the positive electrode and the negative electrode, the battery also comprising a coating arranged between the positive electrode and the separator and / or between the negative electrode and the separator, and the coating is arranged on the surface of at least one of the separator, the positive electrode and the negative electrode.
[0030] In a fourth aspect, the present application provides a vehicle, characterized in that it comprises the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the structure of the battery separator in the embodiment of the present application;
[0032] Figure 2 This is a schematic diagram of the coating structure containing the fibrous first material in an embodiment of the present application;
[0033] Figure 3 This is a schematic diagram of the coating structure containing the granular first material in the embodiment of the present application;
[0034] Figure 4 This is a schematic diagram of the coating structure containing a fibrous first material and a ceramic material in an embodiment of the present application;
[0035] Figure 5 This is a schematic diagram of the coating structure containing a granular first material and a ceramic material in an embodiment of the present application. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0037] See also Figure 1-Figure 5Taking the coating disposed on the separator surface as an example, the battery separator 100 includes a separator base film 10 and a coating 20 disposed on the surface of the separator base film 10. The coating 20 can be disposed on one side or both sides of the separator base film 10. When the coating 20 is disposed on one side of the separator base film 10, the coating 20 is disposed between the positive electrode and the separator base film 10 or between the negative electrode and the separator base film 10. When the coating 20 is disposed on both sides of the separator base film 10, the coating 20 is disposed between the positive electrode and the separator base film 10 and between the negative electrode and the separator base film 10. The coating 20 includes a negative thermal expansion material and / or a zero thermal expansion material 21.
[0038] In the embodiments of the present application, negative thermal expansion material and / or zero thermal expansion material refers to negative thermal expansion material, zero thermal expansion material, or negative thermal expansion material and zero thermal expansion material.
[0039] In the embodiments of the present application, negative thermal expansion materials refer to compounds whose average linear expansion coefficient or volume expansion coefficient is negative within a certain temperature range. Zero thermal expansion materials refer to compounds whose average linear expansion coefficient or volume expansion coefficient is zero within a certain temperature range.
[0040] Since negative thermal expansion materials and zero thermal expansion materials only generate smaller thermal stress when the temperature changes greatly or rapidly, and have better thermal stability, the embodiments of the present application provide a coating containing negative thermal expansion materials and / or zero thermal expansion materials between the positive electrode and the separator and / or between the negative electrode and the separator, which is beneficial to improving the heat resistance and shrinkage resistance of the battery separator and improving the heat shock resistance, so that the lithium-ion battery using the coating can obtain better thermal stability and safety.
[0041] In the embodiment of the present application, the negative thermal expansion material may have an average linear expansion coefficient greater than or equal to -30×10 -6 K -1 and less than 0. In some embodiments of the present application, the negative thermal expansion material and / or zero thermal expansion material 21 may be one or more of ZrW2O8, HfW2O8, ZrMo2O8, AM2O7 (A is at least one of Th, Zr, Hf and Sn, and M is at least one of P and V), but is not limited thereto.
[0042] In the embodiment of the present application, the coating 20 may include only the negative thermal expansion material and / or the zero thermal expansion material 21 , or include the negative thermal expansion material and / or the zero thermal expansion material 21 and the ceramic material 22 .
[0043] The ceramic material 22 may be one or more of aluminum oxide, boehmite, magnesium hydroxide, silicon dioxide, and aluminum silicate, and the average particle size of the ceramic material 22 may range from 0.02um to 100um, and may specifically be 0.02um, 0.05um, 0.1um, 0.5um, 1um, 5um, 10um, 20um, 50um, 70um, and 100um, but is not limited thereto.
[0044] Specifically, the embodiment of the present application can choose to use negative thermal expansion material and / or zero thermal expansion material 21 alone to prepare the coating, and the mass proportion of negative thermal expansion material and / or zero thermal expansion material in the coating can be 63.3%-98.5%. Controlling the volume proportion of negative thermal expansion material and / or zero thermal expansion material in the coating within the above range is conducive to the negative thermal expansion material and / or zero thermal expansion material playing a better role in improving the heat resistance and shrinkage resistance of the battery separator and improving the heat shock resistance of the battery separator.
[0045] The embodiment of the present application can also use negative thermal expansion material and / or zero thermal expansion material 21 and ceramic material 22 to prepare the coating of the battery separator. In the negative thermal expansion material and / or zero thermal expansion material 21 and the ceramic material 22, the mass proportion of the negative thermal expansion material and / or zero thermal expansion material 21 is greater than 0% and less than 100%, and can be specifically 1%, 20%, 50%, 70%, 80%, 90%, etc. The mass proportion of the negative thermal expansion material and / or zero thermal expansion material and the ceramic material in the coating is 63.3%-98.5%. Based on the thermal properties of thermal expansion and contraction of ceramic materials and the thermal properties of thermal contraction and expansion of negative thermal expansion material and / or zero thermal expansion material 21, the embodiment of the present application can obtain a coating material with a suitable average linear expansion coefficient by adjusting the volume proportion of negative thermal expansion material and / or zero thermal expansion material 21 and ceramic material in the coating, so that the obtained battery separator has better heat resistance and shrinkage resistance, higher heat shock resistance, so that the battery has better thermal stability and safety.
[0046] See also Figure 2 and Figure 3 In some embodiments of the present application, negative thermal expansion material and / or zero thermal expansion material 21 are used alone to prepare the coating of the battery separator, that is, the prepared coating contains negative thermal expansion material and / or zero thermal expansion material 21, but does not contain ceramic material 22. Figure 4 and Figure 5 In some embodiments of the present application, negative thermal expansion material and / or zero thermal expansion material 21 and ceramic material 22 are used to prepare the coating of the battery separator, that is, the prepared coating contains negative thermal expansion material and / or zero thermal expansion material 21 and ceramic material 22 at the same time.
[0047] In the embodiment of the present application, the negative thermal expansion material and / or the zero thermal expansion material 21 may be granular, fibrous, or a combination of granular and fibrous. In some embodiments, the negative thermal expansion material and / or the zero thermal expansion material 21 is granular, and the average particle size of the granular negative thermal expansion material and / or the zero thermal expansion material 21 may be 0.01 μm-5 μm, specifically 0.01 μm, 0.02 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, etc. In some embodiments, the negative thermal expansion material and / or zero thermal expansion material 21 is fibrous, and the average fiber diameter of the fibrous negative thermal expansion material and / or zero thermal expansion material can be 10nm-500nm, specifically 10nm, 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, etc.; the average fiber length can be 0.5μm-100μm, specifically 0.5μm, 1μm, 2μm, 5μm, 10μm, 20μm, 30μm, 50μm, 100μm, etc. In some embodiments, the negative thermal expansion material and / or zero thermal expansion material 21 is a combination of granular material and fibrous material. The average particle size of the granular material can be 0.01μm-5μm, specifically 0.01μm, 0.02μm, 0.05μm, 0.08μm, 0.1μm, 0.3μm, 0.5μm, 1μm, 2μm, 3μm, 5μm, etc.; the average fiber diameter of the fibrous material can be 10nm-500nm, specifically 10nm, 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, etc.; the average fiber length can be 0.5μm-100μm, specifically 0.5μm, 1μm, 2μm, 5μm, 10μm, 20μm, 30μm, 50μm, 100μm, etc.
[0048] In the embodiment of the present application, only granular negative thermal expansion material and / or zero thermal expansion material can be used to prepare the coating, only fibrous negative thermal expansion material and / or zero thermal expansion material can be used to prepare the coating, and both granular negative thermal expansion material and / or zero thermal expansion material and fibrous negative thermal expansion material and / or zero thermal expansion material can be used to prepare the coating. The thermal properties brought by the granular negative thermal expansion material and / or zero thermal expansion material and the fibrous negative thermal expansion material and / or zero thermal expansion material due to their own crystal structure are conducive to reducing the thermal stress generated by large or rapid temperature changes, and have good thermal stability. Among them, the long-range structure of the fibrous negative thermal expansion material and / or zero thermal expansion material can further improve the comprehensive performance of the diaphragm. On the one hand, the long-range structure can form a three-dimensional skeleton structure in the coating, enhance the mechanical strength of the diaphragm, and then improve the shrinkage resistance and thermal shock resistance of the battery diaphragm. At the same time, the formed three-dimensional skeleton structure is also beneficial to improve the liquid absorption and liquid retention capacity of the battery diaphragm, thereby better realizing ion conductivity; on the other hand, the fibrous negative thermal expansion material and / or zero thermal expansion material with a long-range structure in the coating that is in contact with the diaphragm base membrane can extend into the pores of the base membrane, so that the surface layer of the diaphragm base membrane close to the coating contains negative thermal expansion material and / or zero thermal expansion material, and the cross-bonding of the fibrous negative thermal expansion material and / or zero thermal expansion material with the base membrane is realized, so that the interface bonding between the coating and the base membrane is tighter, which is beneficial to further improve the shrinkage resistance of the battery diaphragm and improve the thermal stability and safety of lithium-ion batteries at high temperatures. In some embodiments of the present application, when the coating includes fibrous or fibrous and granular negative thermal expansion material and / or zero thermal expansion material, the surface layer of the diaphragm base film close to the coating contains negative thermal expansion material and / or zero thermal expansion material.
[0049] See also Figure 3 and Figure 5 In some embodiments of the present application, a granular negative thermal expansion material and / or a zero thermal expansion material is used to prepare a coating of a battery separator, that is, the coating only includes granular negative thermal expansion material and / or a zero thermal expansion material. Figure 2 and Figure 4 In some other embodiments of the present application, fibrous negative thermal expansion materials and / or zero thermal expansion materials are used to prepare the coating of the battery separator, that is, the coating only includes fibrous negative thermal expansion materials and / or zero thermal expansion materials.
[0050] In the embodiment of the present application, the negative thermal expansion material and / or the zero thermal expansion material are uniformly distributed in the coating. The uniform distribution state is conducive to avoiding the agglomeration of granular negative thermal expansion material and / or zero thermal expansion material or the entanglement of fibrous negative thermal expansion material and / or zero thermal expansion material, thereby facilitating the battery separator to exert more stable heat resistance, shrinkage resistance and heat shock resistance, so that the battery using the battery separator has better thermal stability and safety.
[0051] In the embodiment of the present application, since the coating 20 is a composite of fibrous and / or granular materials, it has a good three-dimensional through-hole structure. This pore structure is beneficial to improving the electrolyte retention capacity, increasing the residual amount of electrolyte, facilitating lithium ion transmission, and improving battery performance.
[0052] The thickness of the coating 20 may be 0.5 μm-5 μm, specifically 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0053] The coating 20 of the embodiment of the present application also includes a binder, which may be one or more of polyvinylidene fluoride, polyvinyl alcohol, acrylonitrile, acrylic resin, phenolic resin, epoxy resin, and silane binder, but is not limited thereto. The mass proportion of the binder in the coating is 1%-35%. Controlling the proportion of the binder in the coating within the above range can ensure that the binder plays an effective bonding role, so that the coating and the base film can be better combined, and at the same time, it can ensure that the coating has a certain content of heat-resistant material, thereby improving the heat resistance and heat shock resistance of the battery separator. The mass proportion of the binder in the coating can specifically be 1%, 5%, 10%, 20%, 30%, 35%, etc.
[0054] In the embodiment of the present application, the diaphragm base film 10 is a polyolefin diaphragm, for example, polyethylene (PE), polypropylene (PP), a multilayer composite diaphragm (PP / PE / PP), etc. In the embodiment of the present application, due to the use of a coating containing a negative thermal expansion material and / or a zero thermal expansion material, the diaphragm base film can exert a relatively stable performance in a relatively thin thickness range of 4μm-12μm, and the thickness of the diaphragm base film can be 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, etc.
[0055] The battery separator provided in the embodiment of the present application has good heat resistance and shrinkage resistance, as well as high heat shock resistance. The above-mentioned battery separator can be used in various types of lithium-ion batteries, such as square batteries, soft-pack batteries, cylindrical batteries, etc., and the battery separator can also be used in other types of batteries such as sodium-ion batteries and magnesium-ion batteries.
[0056] The present invention also provides a method for preparing a coating, comprising the following steps:
[0057] (1) mixing a dispersion of a negative thermal expansion material and / or a zero thermal expansion material with a dispersion of a binder to obtain a coating slurry; or
[0058] Dispersing the ceramic material in the dispersion of the binder to obtain a dispersion of the ceramic material; mixing the dispersion of the negative thermal expansion material and / or the zero thermal expansion material with the dispersion of the ceramic material to obtain a coating slurry;
[0059] (2) The coating slurry is applied to the surface of at least one of the separator, the positive electrode and the negative electrode of the battery, and dried to obtain a coating disposed between the positive electrode and the separator and / or between the negative electrode and the separator of the battery.
[0060] In the embodiment of the present application, the coating slurry can be obtained by mixing a dispersion of a negative thermal expansion material and / or a zero thermal expansion material with a dispersion of a binder.
[0061] Specifically, the dispersion of the binder can be prepared by mixing and stirring a binder, a stabilizer and an organic solvent. The binder includes one or more of polyvinylidene fluoride, polyvinyl alcohol, acrylonitrile, acrylic resin, phenolic resin, epoxy resin, and silane binder, but is not limited thereto. The stabilizer includes one or more of methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, polyamino thickener, sodium polyacrylate, polyvinyl alcohol, and polyacrylamide, but is not limited thereto. The organic solvent includes one or more of N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and acetone, but is not limited thereto.
[0062] In the embodiment of the present application, the mass ratio of the binder to the stabilizer can be 1:0.01-1:0.2, specifically 1:0.01, 1:0.02, 1:0.05, 1:0.1, 1:0.15, 1:0.2, etc. In addition, the embodiment of the present application controls the mass percentage concentration of the dispersion of the binder to 2%-30% by adjusting the amount of organic solvent added, which is not only conducive to ensuring that there is enough binder in the dispersion of the binder to play an effective bonding role, but also conducive to preventing the heat-resistant material in the dispersion of the binder from agglomerating, thereby facilitating better dispersion of the heat-resistant material. In the embodiment of the present application, the mass percentage concentration of the dispersion of the binder can be 2%, 5%, 10%, 20%, 30%, etc.
[0063] In the embodiment of the present application, a planetary mixer is used to stir and mix the binder, stabilizer and organic solvent to obtain a dispersion of the binder. Specifically, the stirring temperature can be 15°C-45°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the stirring time can be 0.5h-2h, specifically 0.5h, 1h, 1.5h, 2h, etc.; the rotation speed of the planetary mixer can be 200rpm-2500rpm, specifically 200rpm, 500rpm, 1000rpm, 1500rpm, 2000rpm, 2500rpm, etc., and the revolution speed can be 5rpm-100rpm, specifically 5rpm, 10rpm, 20rpm, 50rpm, 100rpm, etc.
[0064] In the embodiment of the present application, the dispersion of negative thermal expansion material and / or zero thermal expansion material is prepared by mixing and stirring negative thermal expansion material and / or zero thermal expansion material, dispersant and organic solvent. Wherein, negative thermal expansion material and / or zero thermal expansion material include one or more of ZrW2O8, HfW2O8, ZrMo2O8, AM2O7 (A is Th, Zr, Hf or Sn, M is P or V), but not limited to this, the negative thermal expansion material and / or zero thermal expansion material can be granular or fibrous. Dispersant is mixed by coupling agent and surfactant, wherein, coupling agent includes but is not limited to one or more of chromium complex coupling agent, silane coupling agent, titanate coupling agent, aluminate coupling agent, surfactant includes but is not limited to one or more of stearic acid, sodium dodecyl phenyl yellow acid, quaternary ammonium compound, lecithin, fatty acid glyceride, polysorbate, etc. Organic solvent includes one or more of N-methyl pyrrolidone, dimethylacetamide, dimethylformamide, acetone, but not limited to this.
[0065] In the embodiment of the present application, adding a dispersant to the dispersion of the negative thermal expansion material and / or the zero thermal expansion material is beneficial to make the negative thermal expansion material and / or the zero thermal expansion material dispersed more evenly, so that the negative thermal expansion material and / or the zero thermal expansion material are distributed more evenly in the prepared coating; on the other hand, it is also beneficial to prevent the fibrous negative thermal expansion material and / or the zero thermal expansion material with a long-range structure from entanglement and the like, so that the fibrous negative thermal expansion material and / or the zero thermal expansion material can not only be more easily dispersed evenly in the coating slurry, but also better form a three-dimensional skeleton structure, thereby improving the comprehensive performance of the battery separator. In the embodiment of the present application, the mass ratio of the negative thermal expansion material and / or the zero thermal expansion material to the dispersant can be 1:0.005-1:0.08, specifically 1:0.005, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, etc.
[0066] In the embodiment of the present application, a planetary mixer is used to stir the negative thermal expansion material and / or the zero thermal expansion material, the dispersant and the organic solvent to obtain the dispersion of the negative thermal expansion material and / or the zero thermal expansion material. Wherein, the stirring temperature can be 15°C-45°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the stirring time can be 0.5h-2h, specifically 0.5h, 1h, 1.5h, 2h, etc.; the rotation speed of the planetary mixer can be 100rpm-500rpm, specifically 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, etc., and the revolution speed can be 5rpm-100rpm, specifically 5rpm, 10rpm, 20rpm, 50rpm, 100rpm, etc. The embodiment of the present application is stirred within the above-mentioned lower stirring speed range, which is conducive to obtaining a better dispersion effect of the negative thermal expansion material and / or the zero thermal expansion material. Since the fibrous negative thermal expansion material and / or zero thermal expansion material with a long-range structure can form a three-dimensional skeleton structure, controlling the stirring speed at the above-mentioned lower level is also beneficial to ensure the structural integrity of the fibrous negative thermal expansion material and / or zero thermal expansion material, thereby helping to improve the shrinkage resistance and heat shock resistance of the battery separator, while improving the liquid absorption and liquid retention capacity of the battery separator.
[0067] In the embodiment of the present application, the dispersion of the above-mentioned negative thermal expansion material and / or zero thermal expansion material is mixed with the dispersion of the above-mentioned binder, and the coating slurry is obtained after sieving. In the coating slurry, the mass ratio of the binder to the negative thermal expansion material and / or zero thermal expansion material can be 0.01:1-0.5:1, specifically 0.01:1, 0.1:1, 0.3:1, 0.4:1, 0.5:1, etc.
[0068] The embodiment of the present application adopts a planetary mixer to stir the dispersion of negative thermal expansion material and / or zero thermal expansion material and the dispersion of binder to obtain the above-mentioned coating slurry. Wherein, the stirring temperature can be 15℃-45℃, specifically 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, etc.; the stirring time can be 0.5h-2h, specifically 0.5h, 1h, 1.5h, 2h, etc.; the rotation speed of the planetary mixer can be 100rpm-500rpm, specifically 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, etc., and the revolution speed can be 5rpm-100rpm, specifically 5rpm, 10rpm, 20rpm, 50rpm, 100rpm, etc.
[0069] In the embodiment of the present application, the ceramic material may be first dispersed in a dispersion of a binder to obtain a dispersion of the ceramic material; and then the dispersion of a negative thermal expansion material and / or a zero thermal expansion material is mixed with the dispersion of the ceramic material to obtain a coating slurry.
[0070] Specifically, the dispersion of the ceramic material is prepared by dispersing the ceramic material in the dispersion of the binder. The ceramic material includes one or more of aluminum oxide, boehmite, magnesium hydroxide, silicon dioxide, and aluminum silicate, but is not limited thereto. In the dispersion of the ceramic material, the mass ratio of the binder to the ceramic material can be 0.01:1-0.5:1, specifically 0.01:1, 0.1:1, 0.3:1, 0.4:1, 0.5:1, etc.
[0071] The dispersion of the ceramic material in the dispersion of the binder can be carried out by stirring and dispersing, for example. In the embodiment of the present application, a planetary mixer is used for stirring and dispersing, and the dispersion temperature can be 15°C-45°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the dispersion time can be 0.5h-2h, specifically 0.5h, 1h, 1.5h, 2h, etc.; the rotation speed of the planetary mixer can be 200rpm-2500rpm, specifically 200rpm, 500rpm, 1000rpm, 1500rpm, 2000rpm, 2500rpm, etc., and the revolution speed can be 5rpm-100rpm, specifically 5rpm, 10rpm, 20rpm, 50rpm, 100rpm, etc.
[0072] In an embodiment of the present application, the dispersion of the ceramic material is mixed with the dispersion of the negative thermal expansion material and / or the zero thermal expansion material, and the coating slurry is obtained after sieving. In the coating slurry, the proportion of the negative thermal expansion material and / or the zero thermal expansion material relative to the total mass of the negative thermal expansion material and / or the zero thermal expansion material and the ceramic material can be greater than 0 and less than 100%, and can be specifically 1%, 20%, 50%, 70%, 80%, 90%, etc.
[0073] The embodiment of the present application adopts a planetary mixer to stir the dispersion of negative thermal expansion material and / or zero thermal expansion material and the dispersion of ceramic material to obtain the above-mentioned coating slurry. Wherein, the stirring temperature can be 15°C-45°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the stirring time can be 0.5h-2h, specifically 0.5h, 1h, 1.5h, 2h, etc.; the rotation speed of the planetary mixer can be 100rpm-500rpm, specifically 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, etc., and the revolution speed can be 5rpm-100rpm, specifically 5rpm, 10rpm, 20rpm, 50rpm, 100rpm, etc.
[0074] In the implementation mode of the present application, the coating slurry prepared as above is coated on the diaphragm base film and dried to obtain a battery diaphragm. In the embodiment of the present application, the coating can be performed on one or both sides of the surface of the diaphragm base film, and the number of coatings can be one or more times. After the coating is completed, a drying treatment is performed to obtain a battery diaphragm with a coating on the surface of the base film. The preparation method of the battery can be a method known in the art. In some embodiments of the present application, the positive electrode sheet, the negative electrode sheet, the electrolyte and the diaphragm are wound or stacked to form a pole core, which is placed in a battery housing and sealed to obtain a battery. In other embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the diaphragm are wound or stacked to form a pole core, which is placed in a battery housing, an electrolyte is added, and the battery is obtained.
[0075] The above-mentioned diaphragm base film can be polyethylene (PE), polypropylene (PP) or a multi-layer composite diaphragm (PP / PE / PP), and the thickness of the diaphragm base film can be 4μm-12μm, specifically 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, etc. The coating speed in the above-mentioned coating process can be 10m / min-50m / min, specifically 10m / min, 20m / min, 30m / min, 40m / min, 50m / min, etc. The drying temperature in the above-mentioned drying process can be 50℃-80℃, specifically 50℃, 60℃, 70℃, 80℃, etc.; the drying time can be 2min-10min, specifically 2min, 5min, 10min, etc. The coating thickness obtained after coating and drying can be 0.5 μm-5 μm, specifically 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0076] The preparation method provided in the embodiments of the present application has low cost and high efficiency and is suitable for large-scale production.
[0077] In the battery of the embodiment of the present application, the positive electrode includes a positive electrode collector and a positive electrode active material, a binder and a conductive agent loaded on the positive electrode collector. The positive electrode collector can be an aluminum foil, and the positive electrode active material can adopt all the positive electrode active materials that can be commercially used so far, including but not limited to LiFePO4, LiMnO2, LiNiO2, LiCoO2, LiVPO4F, LiFeO2 and ternary positive electrode active materials.
[0078] The negative electrode includes a negative electrode current collector and a negative electrode active material loaded on the negative electrode current collector, a binder and a conductive agent. The negative electrode current collector can be copper foil, and the negative electrode active material can adopt all negative electrode materials that can be commercially used so far, including but not limited to one or more of natural graphite, artificial graphite, hard carbon, soft carbon, and lithium titanate.
[0079] The binder may be any binder known in the art, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber and polyacrylate; the conductive agent may be any conductive agent known in the art, including but not limited to one or more of single-walled carbon nanotubes, graphite, carbon fiber, carbon black, metal powder, metal oxide and fiber.
[0080] The battery provided in the embodiments of the present application has good thermal stability and safety.
[0081] Although the battery of the present application, especially the arrangement of the coating in the battery, is described in terms of structure and effect by taking the above example that the coating is arranged on the surface of the separator and the separator is a diaphragm base film, those skilled in the art should understand that when the coating is arranged on the surface of the positive electrode and / or the negative electrode, since the coating is still arranged between the separator and the positive electrode and / or the negative electrode, the coating can still exert the above effect. No further explanation is given here.
[0082] The present application also provides a vehicle, which includes the battery provided in the embodiment of the present application. The battery provided in the embodiment of the present application can improve the safety of the vehicle.
[0083] The implementation scheme of the present application is further described below with multiple examples.
[0084] Example 1
[0085] A method for preparing a lithium ion battery comprises the following steps:
[0086] (1) adding a binder, a stabilizer and an organic solvent into a planetary mixer and mixing and stirring to obtain a 2 wt % binder dispersion;
[0087] The binder is a mixture of polyvinylidene fluoride and silane binder in a mass ratio of 1:1; the stabilizer is a mixture of methyl cellulose and polyvinyl alcohol in a mass ratio of 1:1; the organic solvent is N-methylpyrrolidone; the mass ratio of the binder to the stabilizer is 1:0.01; the stirring temperature is 15°C, the stirring time is 0.5h, the rotation speed of the planetary mixer is 200rpm, and the revolution speed is 5rpm;
[0088] (2) adding a negative thermal expansion and / or zero thermal expansion material, a dispersant and an organic solvent into a planetary mixer for mixing and stirring to obtain a dispersion of the negative thermal expansion and / or zero thermal expansion material;
[0089] Wherein, the negative thermal expansion and / or zero thermal expansion material is a fibrous negative thermal expansion and / or zero thermal expansion material ZrW2O8, with an average diameter of 10 nm and an average length of 0.5 μm; the dispersant is a mixture of a silane coupling agent and a sodium dodecylbenzene sulfonate surfactant in a mass ratio of 9:1; the mass ratio of the negative thermal expansion and / or zero thermal expansion material to the dispersant is 1:0.005; the stirring temperature is 15°C, the stirring time is 0.5 h, the rotation speed of the planetary mixer is 100 rpm, and the revolution speed is 5 rpm;
[0090] (3) adding the dispersion of the negative thermal expansion and / or zero thermal expansion material to the dispersion of the binder, mixing and stirring, and sieving to obtain a coating slurry;
[0091] The mass ratio of the binder to the negative thermal expansion and / or zero thermal expansion material is 0.05:1; the stirring temperature is 15°C, the stirring time is 0.5h, the rotation speed of the planetary mixer is 100rpm, and the revolution speed is 5rpm;
[0092] (4) coating the coating slurry on both sides of the separator base film and drying the coating slurry to obtain a battery separator;
[0093] Among them, the diaphragm base film is polyethylene (PE), and the thickness of the diaphragm base film is 6μm; the coating speed during the coating process is 25m / min, and the thickness of each coating after coating is 2μm; the drying temperature is 50°C, and the drying time is 2min.
[0094] (5) The lithium cobalt oxide positive electrode, the graphite negative electrode and the battery separator prepared in step (4) are made into a battery cell, which is loaded into a battery shell and sealed to obtain a battery.
[0095] Among them, the preparation method of lithium cobalt oxide positive electrode is: lithium cobalt oxide powder, binder polyvinylidene fluoride (PVDF), conductive agent carbon nanotube (CNT), carbon black mixture and N-methylpyrrolidone (NMP) solution are evenly dispersed by a mixer according to a mass ratio of 100:2.5:12:0.3:55, and then coated on Al foil, and then baked, rolled and cut into lithium cobalt oxide positive electrode sheets.
[0096] The preparation method of the graphite negative electrode is as follows: graphite powder, styrene-butadiene rubber (SBR) emulsion, carboxymethyl cellulose (CMC) solution, carbon black conductive agent, and water are evenly dispersed by a mixer in a mass ratio of 100:2.5:1.5:3:130, and then coated on Cu foil, and then baked, rolled, and cut into graphite negative electrode sheets.
[0097] The assembly steps of the battery are as follows: in an inert atmosphere with a water content of less than 5ppm, the above-mentioned lithium cobalt oxide positive electrode, battery separator and graphite negative electrode are stacked in order and wound into a bare battery cell, the bare battery cell is loaded into a battery shell and welded, and then the electrolyte is injected into the battery shell for formation to make a battery.
[0098] Example 2
[0099] A method for preparing a lithium ion battery, which differs from Example 1 only in that the average length of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 30 μm.
[0100] Example 3
[0101] A method for preparing a lithium ion battery, which differs from Example 1 only in that the average length of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 50 μm.
[0102] Example 4
[0103] A method for preparing a lithium ion battery, which differs from Example 1 only in that the average length of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 100 μm.
[0104] Example 5
[0105] A method for preparing a lithium ion battery, which differs from Example 1 only in that the average length of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 0.1 μm.
[0106] Example 6
[0107] A method for preparing a lithium ion battery, which differs from Example 1 only in that the average length of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 150 μm.
[0108] Example 7
[0109] A method for preparing a lithium ion battery, which differs from Example 1 only in that the negative thermal expansion and / or zero thermal expansion material in step (2) is a granular negative thermal expansion and / or zero thermal expansion material ZrW2O8 with an average diameter of 0.5 μm.
[0110] Example 8
[0111] A method for preparing a lithium ion battery, which differs from Example 1 only in that the negative thermal expansion and / or zero thermal expansion material in step (2) is a fibrous negative thermal expansion and / or zero thermal expansion material ZrMo2O8.
[0112] Example 9
[0113] A method for preparing a lithium ion battery, which differs from Example 1 only in that the mass ratio of the binder to the negative thermal expansion and / or zero thermal expansion material in step (3) is 0.3:1.
[0114] Example 10
[0115] A method for preparing a lithium ion battery, which differs from Example 1 only in that in step (2), the mass ratio of the negative thermal expansion and / or zero thermal expansion material to the dispersant is 1:0.05.
[0116] Embodiment 11
[0117] A method for preparing a lithium ion battery, which differs from Example 1 only in that the dispersant in step (2) is a mixture of a titanate coupling agent and a fatty acid glyceride surfactant.
[0118] Example 12
[0119] A method for preparing a lithium ion battery, which differs from Example 1 only in that, after step (1) and before step (2), it further comprises adding a ceramic material to a dispersion of a binder and dispersing the mixture in a planetary mixer to obtain a dispersion of the ceramic material;
[0120] Among them, the ceramic material is aluminum oxide with an average particle size of 50nm; the mass ratio of the binder to the ceramic material is 0.05:1; the dispersion temperature is 15°C, the dispersion time is 0.5h, the rotation speed of the planetary mixer is 200rpm, and the revolution speed is 5rpm.
[0121] Example 13
[0122] A method for preparing a lithium ion battery, which differs from Example 2 only in that the average diameter of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 200 nm.
[0123] Embodiment 14
[0124] A method for preparing a lithium ion battery, which differs from Example 2 only in that the average diameter of the fibrous negative thermal expansion and / or zero thermal expansion material in step (2) is 500 nm.
[0125] Embodiment 15
[0126] A method for preparing a lithium ion battery, which differs from Example 1 only in that the coating slurry is coated on the negative electrode sheet and dried. The coating thickness after coating is 4 μm.
[0127] Example 16
[0128] A method for preparing a lithium ion battery, which differs from Example 2 only in that the coating thickness after coating in step (4) is 0.5 μm.
[0129] Embodiment 17
[0130] A method for preparing a lithium ion battery, which differs from Example 2 only in that the coating thickness after coating in step (4) is 5 μm.
[0131] Embodiment 18
[0132] A method for preparing a lithium ion battery, which differs from Example 1 only in that no dispersant is added in step (2).
[0133] Embodiment 19
[0134] A method for preparing a lithium-ion battery, which differs from Example 1 only in that the coating slurry is coated on one side of the separator base film facing the positive electrode; the coating thickness after coating is 4 μm.
[0135] Embodiment 20
[0136] A method for preparing a lithium-ion battery, which differs from Example 1 only in that the negative thermal expansion and / or zero thermal expansion material is composed of fibrous ZrW2O8 and granular ZrW2O8 in a mass ratio of 1:1, the average diameter of the fibrous ZrW2O8 is 10nm, and the average length is 0.5μm; the average diameter of the granular ZrW2O8 is 0.5μm.
[0137] In order to highlight the beneficial effects of this application, the following comparative examples are now provided:
[0138] Comparative Example 1
[0139] A lithium-ion battery, which has the same diaphragm base film as that in Example 1, that is, a polyethylene (PE) battery diaphragm, has a diaphragm thickness of 6 μm, and has no coating layer on the diaphragm surface.
[0140] Comparative Example 2
[0141] A lithium ion battery, which differs from Example 12 in that the negative thermal expansion and / or zero thermal expansion material in Example 12 is replaced by an aluminum oxide ceramic material with an average particle size of 50 nm.
[0142] In order to highlight the beneficial effects of the embodiments of the present application, the obtained battery was subjected to a battery thermal abuse test and a collision performance test. The test results are shown in Table 1 below. The test method is:
[0143] Thermal abuse test: According to the test method in the IEC62133 standard, the test batteries are placed under battery thermal abuse at 132°C, 134°C, and 136°C for 1 hour. Five identical batteries are tested and the number of batteries that pass the test is calculated.
[0144] Collision test: According to the test method in UN38.3 standard, 32 identical batteries are tested and the number of batteries that pass the test is calculated.
[0145] Table 1
[0146]
[0147] It can be seen from Table 1 above that, compared with Comparative Example 1, the lithium-ion batteries prepared in Examples 1-20 using battery separators containing negative thermal expansion and / or zero thermal expansion materials in the coating have more battery thermal abuse test pass numbers and collision performance test pass numbers, indicating that the use of negative thermal expansion and / or zero thermal expansion materials in the separator coating can effectively improve the heat resistance of the battery separator, improve the heat shock resistance of the battery separator, and thereby improve the thermal stability and safety of the battery.
[0148] Compared with Example 18, Example 1 adds a dispersant during the preparation of the dispersion of the negative thermal expansion and / or zero thermal expansion material, so that the negative thermal expansion and / or zero thermal expansion material can be evenly dispersed in the dispersion of the negative thermal expansion and / or zero thermal expansion material, thereby achieving a uniform distribution of the negative thermal expansion and / or zero thermal expansion material in the diaphragm coating, which is conducive to giving full play to the role of the negative thermal expansion and / or zero thermal expansion material and / or zero thermal expansion material in improving the heat resistance of the battery diaphragm and improving the heat shock resistance of the battery diaphragm, so that the lithium-ion battery using the battery diaphragm has better thermal stability and safety.
[0149] Compared with Comparative Example 2, the coating of Example 12 includes negative thermal expansion and / or zero thermal expansion materials in addition to ceramic materials, thereby greatly improving the heat resistance and heat shock resistance of the battery separator.
[0150] It can be seen from Examples 1-6 that the average fiber length of the fibrous negative thermal expansion and / or zero thermal expansion material is relatively longer, and a more complete three-dimensional skeleton structure can be formed in the coating, so that the battery separator has better heat resistance and higher heat shock resistance, which is conducive to giving full play to the advantages of the long-range structure of the fibrous negative thermal expansion and / or zero thermal expansion material and better improving the overall performance of the battery.
[0151] Compared with the fibrous negative thermal expansion and / or zero thermal expansion material with an average length of 0.5 μm in Example 1, the granular negative thermal expansion and / or zero thermal expansion material with an average diameter of 0.5 μm is used to prepare the diaphragm coating in Example 7. The results show that the number of batteries that passed the battery thermal abuse test and the number of batteries that passed the collision performance test in Example 1 are higher than those in Example 7, indicating that the long-range structure of the fibrous negative thermal expansion and / or zero thermal expansion material is conducive to better improving the heat resistance of the battery diaphragm and improving the heat shock resistance of the battery diaphragm.
[0152] Example 8 uses a negative thermal expansion and / or zero thermal expansion material different from that of Example 1, and Example 11 uses a dispersant different from that of Example 1, but the batteries in Examples 8 and 11 both show comprehensive performance that is equivalent to or close to that of Example 1, indicating that the diaphragm preparation method provided in the present application can enable the battery diaphragm to obtain better comprehensive performance.
[0153] Compared with Example 1, the mass ratio of the binder to the negative thermal expansion and / or zero thermal expansion material in Example 9 is higher. The number of batteries that pass the thermal abuse test and the number of batteries that pass the collision performance test in Example 9 are both increased relative to those in Example 1. This is mainly because the increase in the binder improves the peeling force of the coating and the stability of the three-dimensional structure, which is beneficial to improving the heat resistance and heat shock resistance.
[0154] Compared with Example 18, dispersants were added to Example 1 and Example 10 when preparing the coating slurry. The mass ratio of the dispersant to the negative thermal expansion and / or zero thermal expansion material in Example 10 was higher than that in Example 1. The number of batteries that passed the thermal abuse test and the number of batteries that passed the collision performance test in Examples 1 and 10 were increased relative to that in Example 18. The number of batteries that passed the thermal abuse test and the number of batteries that passed the collision performance test in Example 10 was slightly increased relative to that in Example 1. This is mainly because the addition of the dispersant improves the dispersion of the negative thermal expansion and / or zero thermal expansion material, which is beneficial to improving the three-dimensional structural stability, and is beneficial to improving the heat resistance and heat shock strength.
[0155] In Example 12, negative thermal expansion and / or zero thermal expansion materials are mixed with ceramic materials to prepare the diaphragm coating. Since the ceramic material in the coating has a positive thermal expansion coefficient, the overall thermal expansion coefficient is higher than that of Example 1, so that the battery diaphragm in Example 1 exhibits better comprehensive performance at high temperatures.
[0156] Examples 2, 13, and 14 use fibrous negative thermal expansion and / or zero thermal expansion materials with different average diameters. It can be seen from the test results in Table 1 that Example 2 shows better overall battery performance than Examples 13 and 14. This is mainly because the fibrous material has a small diameter, which is conducive to forming a stronger interface bond with the diaphragm base film material. As the diameter of the fibrous material increases, the interface bonding force between the fibrous material and the diaphragm base film material will weaken. At the same time, the three-dimensional structural stability of the fibrous material will also deteriorate, thereby deteriorating the thermal stability of the diaphragm material and the overall performance of the battery.
[0157] Compared with Example 1, Example 15 coated the coating on the surface of the negative electrode, and there was no significant difference in the overall performance of the battery, which shows that the coating can also be effective when applied on the surface of the negative electrode.
[0158] Examples 2, 16, and 17 use coatings of different thicknesses. It can be seen from the results in Table 1 that within a suitable thickness range, as the coating thickness increases, more negative thermal expansion and / or zero thermal expansion materials are present on a single surface of the diaphragm, which significantly enhances the heat resistance of the battery diaphragm and improves the heat shock resistance of the battery diaphragm, thereby making the battery have better overall performance.
[0159] Compared with Example 1, Example 19 only applies the coating on one side of the diaphragm, but the total thickness of the coating in the battery remains unchanged, and there is no significant difference in the overall performance of the battery.
[0160] Compared with Example 1, Example 20 uses a combination of fibrous ZrW2O8 and granular ZrW2O8 in a mass ratio of 1:1 as negative thermal expansion and / or zero thermal expansion materials. Since the long-range structure of the fibrous negative thermal expansion and / or zero thermal expansion materials is beneficial to better improve the heat resistance of the battery separator and improve the heat shock strength of the battery separator, the number of batteries that pass the thermal abuse test and the number of batteries that pass the collision performance test of Example 1 are higher than those of Example 20.
Claims
1. A coating suitable for a battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The coating includes a negative thermal expansion material and / or a zero thermal expansion material, wherein the negative thermal expansion material and / or the zero thermal expansion material is at least one of ZrW2O8, HfW2O8, ZrMo2O8 and AM2O7, A is at least one of Th, Zr, Hf and Sn, and M is at least one of P and V. The negative thermal expansion material and / or the zero thermal expansion material includes a fibrous material, the average diameter of the fibrous material is 10nm-500nm, and the average length of the fibrous material is 0.5μm-100μm; the coating is arranged between the positive electrode and the separator and / or between the negative electrode and the separator, and the coating is arranged on the surface of at least one of the separator, the positive electrode and the negative electrode.
2. The coating according to claim 1, wherein The negative thermal expansion material and / or zero thermal expansion material is a combination of granular material and fibrous material; the average particle size of the granular material is 0.01 μm-5 μm; the average fiber diameter of the fibrous material is 10 nm-500 nm, and the average fiber length is 0.5 μm-100 μm.
3. The coating according to claim 2, wherein The surface layer of at least one of the separator, the positive electrode and the negative electrode close to the coating layer contains the negative thermal expansion material and / or the zero thermal expansion material.
4. The coating according to claim 1, wherein The average linear expansion coefficient a of the negative thermal expansion material in the temperature range of 25°C to 600°C satisfies: -30×10 -6 K -1 ≤a<0.
5. The coating according to claim 1, wherein The mass proportion of the negative thermal expansion material and / or zero thermal expansion material in the coating is 63.3%-98.5%.
6. The coating according to claim 1, wherein The coating further includes a ceramic material, and the mass proportion of the negative thermal expansion material and / or zero thermal expansion material and the ceramic material in the coating is 63.3%-98.5%; the ceramic material is at least one of aluminum oxide, boehmite, magnesium hydroxide, silicon dioxide and aluminum silicate.
7. The coating according to claim 1, wherein The coating also includes a binder, and the mass proportion of the binder in the coating is 1%-35%; the coating forms a porous structure; and the thickness of the coating is 0.5 μm-5 μm.
8. A method for preparing a coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Dispersing and mixing the negative thermal expansion material and / or the zero thermal expansion material with the binder to obtain a coating slurry; or Dispersing and mixing the ceramic material, the negative thermal expansion material and / or the zero thermal expansion material with the binder to obtain a coating slurry; The coating slurry is applied to the surface of at least one of the separator, the positive electrode and the negative electrode of the battery, and dried to obtain a coating disposed between the positive electrode and the separator and / or between the negative electrode and the separator of the battery.
9. The preparation method according to claim 8, wherein The coating slurry contains a dispersant, and the mass ratio of the negative thermal expansion material and / or zero thermal expansion material to the dispersant is 1:0.005-1:0.08; The dispersant includes a coupling agent and a surfactant; the coupling agent is at least one of a chromium coupling agent, a silane coupling agent, a titanate coupling agent and an aluminate coupling agent; the surfactant is at least one of stearic acid, sodium dodecylbenzenesulfonate, a quaternary ammonium compound, lecithin, fatty acid glyceride and polysorbate.
10. A battery comprising a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode, characterized in that: The battery further includes a coating disposed between the positive electrode and the separator and / or between the negative electrode and the separator, and the coating is disposed on the surface of at least one of the separator, the positive electrode, and the negative electrode, and the coating is the coating according to any one of claims 1 to 7.
11. A vehicle, characterized in that: A battery comprising the battery of claim 10.
Citation Information
Patent Citations
Composite ceramic diaphragm for battery and preparation method thereof, and battery
CN109546060A
Functional diaphragm of electrochemical device, preparation method of functional diaphragm and electrochemical device
CN114512770A
All-solid type lithium secondary battery and power storage device
JP2016076359A